La peau de chagrin - Kristl, Vlado; Vrbanic, Ivo (Yugoslavia, 1960)
Cartoon based on the short story by Honoré de Balzac. A man is suicidal, in part because of gambling debts. Death, in disguise, gives him a deal: he is given a magic square of some material; it will grant all his wishes, but it will shrink as will his remaining time. As time runs out, he and his lover get desperate, but to no avail.
The film is contained with other pieces by Kristl: Kradja dragulja 1959, (9 min.), Don Kihot 1961, (11 min.), General i resni clovek 1962, (10 min.), Madeleine, Madeleine 1963, (10 min.), Der Damm 1964, (77 min.), Prometheus 1966, (10 min.), Italienisches Capriccio 1969, (28 min.), Film oder Macht 1970, (101 min.), Tigerkäfig 1971, (14 min.).
Languages: German, French, English. Options for the subtitles: German, French, English.